Trends and collaborations in discoid lupus erythematosus research: a bibliometric analysis from 2010 to 2024 - Zhang, Daichao; Liang, Chaoran; Yin, Qiuyue; Li, Yatong (Frontiers in Medicine, 2025)
IntroductionDiscoid lupus erythematosus (DLE) is a chronic autoimmune skin disorder. Research fragmentation in DLE limits cohesive clinical and scientific progress. This bibliometric analysis aimed to clarify publication trends, collaboration networks, and emergent research themes in DLE from 2010 to 2024.MethodsA comprehensive search of the Web of Science Core Collection (WoSCC) used the terms “discoid lupus erythematosus” OR “lupus erythematosus discoid.” English-language articles and reviews (n = 861) were identified and analyzed via the Bibliometrix package in R to examine annual output, authorship, core journals, and keywords evolution.ResultsAnnual publications increased notably after 2018, although average citation rates declined. A small group of prolific authors, led by WERTH VP, contributed disproportionately. The United States dominated publication volume and international collaboration, followed by Italy, the United Kingdom, Germany, and China. Keywords analysis showed a shift from initial emphasis on disease classification and diagnosis toward advanced therapies, immunological mechanisms.ConclusionDespite growing interest in DLE, it remains underrepresented compared with systemic lupus erythematosus. Broader collaborations, refined diagnostic criteria, and robust clinical trials are essential to enhance therapeutic strategies and patient outcomes in DLE.